2008
DOI: 10.1124/mol.108.047365
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib Resistance in HCT116 Cells Is Mediated by Elevated MCL-1 Expression and Decreased BAK Activation and Not by ERBB Receptor Kinase Mutation

Abstract: We have defined some of the mechanisms by which the kinase inhibitor lapatinib kills HCT116 cells. Lapatinib inhibited radiationinduced activation of ERBB1/2, extracellular signal-regulated kinases 1/2, and AKT, and radiosensitized HCT116 cells. Prolonged incubation of HCT116 cells with lapatinib caused cell killing followed by outgrowth of lapatinib-adapted cells. Adapted cells were resistant to serum starvation-induced cell killing and were cross-resistant to multiple therapeutic drugs. Lapatinib was compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 55 publications
1
63
0
Order By: Relevance
“…Products of many of the anti-apoptotic YB-1 target genes have previously been implicated in drug resistance. For example, inhibition of inhibitor of apoptosis-family members cIAP1 (BIRC2) and cIAP2 (BIRC3) increases apoptosis in response to trastuzumab, lapatinib or gefitinib in HER2-overexpressing cells (Foster et al, 2009), whereas inhibition of MCL-1 sensitizes cells to both lapatinib and trastuzumab (Henson et al, 2006;Martin et al, 2008). Moreover, TNFSF18 and TCF7L1 are associated with tamoxifen and erlotinib resistance, respectively (Treeck et al, 2004;Halatsch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Products of many of the anti-apoptotic YB-1 target genes have previously been implicated in drug resistance. For example, inhibition of inhibitor of apoptosis-family members cIAP1 (BIRC2) and cIAP2 (BIRC3) increases apoptosis in response to trastuzumab, lapatinib or gefitinib in HER2-overexpressing cells (Foster et al, 2009), whereas inhibition of MCL-1 sensitizes cells to both lapatinib and trastuzumab (Henson et al, 2006;Martin et al, 2008). Moreover, TNFSF18 and TCF7L1 are associated with tamoxifen and erlotinib resistance, respectively (Treeck et al, 2004;Halatsch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our prior studies demonstrated that obatoclax potentiated the cytotoxicity of lapatinib in human colon and breast cancer cells by inducing autophagic cell death (Martin et al, 2008. In the present article, we have endeavored to explore the mechanism by which obatoclax and lapatinib interacted to cause toxic autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to lapatinib monotherapy, coadministration of lapatinib with the BCL-2/BCL-XL/MCL-1 antagonist obatoclax (GX-15-070) attenuated lapatinib resistance and produced synergistic cancer cell killing by eliciting autophagic cell death in a wide range of human breast and colon cancer cells (Martin et al, 2008Mitchell et al, 2010). However, molecular mechanisms by which obatoclax and lapatinib interact to cause toxic autophagy have not been fully described or understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve greater effects on survival, inhibition of multiple growth factor receptors and intracellular pathways has to be targeted. It has been noted that tumors presenting with alterations in ERBB receptors are often more aggressive and frequently convey poorer clinical outcome (Bigner and Vogelstein, 1990;Hynes and Lane, 2005;Martin et al, 2008). In addition, it is known that medulloblastoma and malignant glioma often exhibit expres-sion of constitutively activated or altered ERBB receptors; therefore, the use of small molecule kinase inhibitors, such as lapatinib and gefitinib, as anticancer therapeutics in CNS tumor types is logical (Miller, 2004;Hynes and Lane, 2005).…”
Section: Introductionmentioning
confidence: 99%